FACTORS THAT INFLUENCE OWNERSHIP ON THE INCIDENCE OF DIARRHEA IN THE AREA OF PEMATANG CENGAL COMMUNITY HEALTH CENTER, LANGKAT REGENCY - Nanda, Meutia; Anggita, Dwi; Khathimah, Husnul; Masyithah, Ruhul; Harahap, Dwi Adelia Putri (HEARTY, 2025)
Diarrhea is a condition where a person defecates more than 3 times a day. Diarrhea is still one of the public health problems that is of concern because it is the third major contributor to child morbidity and mortality in various developing countries including Indonesia. This study aims to determine the effect of latrine sanitation variables and defecation behavior on the incidence of diarrhea in Pematang Cengal village. The research method is a quantitative study using an analytical survey design with a Cross-Sectional approach. From the total population obtained, 3452 residents were obtained samples received from Pemantang Cengal Village were 97 respondents using the slovin formula. This study utilized instruments using secondary data from the Pematang Cengal Village Health Center. Data were analyzed using SPSS to test the Univariate, Bivariate and Multivariate analysis hypotheses using the chi square statistical test at a significance level of 95% (p-Value <0.05). The results obtained from 6 research variables conducted, there are 5 variables that have a relationship, namely ownership of a decent toilet (0.001), the distance of the toilet is at least 10 m from the water source (0.001), the toilet has a cover (0.007), the toilet has a septic tank (0.000), and the behavior of defecating in a private toilet (0.007). While the variable that has no effect is the habit of washing hands after defecating has no effect (0.057> 0.005). The multivariate results show that the variable of ownership of a septic tank has the most influence on the incidence of diarrhea with an OR value = 1.56. The conclusion is that ownership of a decent toilet, the distance of the toilet is at least 10 m from the water source, the toilet has a cover, the toilet has a septic tank, and the behavior of defecating in a private toilet are behaviors that prevent the transmission of diarrhea in Pematang Cengal Village. Overall, this study emphasizes the importance of ownership and use of healthy toilets and a good sanitation system to prevent the incidence of diarrhea in the community.